2019
DOI: 10.1038/s41598-019-54724-8
|View full text |Cite
|
Sign up to set email alerts
|

Micromechanical Response of Crystalline Phases in Alternate Cementitious Materials using 3-Dimensional X-ray Techniques

Abstract: Cementitious materials are complex composites that exhibit significant spatial heterogeneity in their chemical composition and micromechanical response. Modern 3-dimensional characterization techniques using X-rays from synchrotron light sources, such as micro-computed tomography (μCT) and far-field high-energy diffraction microscopy (ff-HEDM), are now capable of probing this micromechanical heterogeneity. In this work, the above mentioned techniques are used to understand the varying micromechanical response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…In the system described by Vonk et al (97), deformations and interlayer damage development can be tracked under controlled conditions of humidity in a cardboard. Using a combination of micro-computed tomography and far-field high-energy diffraction, Nair et al (98) track stress partitioning in individual grains of a cement-quartz mixture, demonstrating that the loss of a diffraction peak from a grain can signal the onset of fracture in these granular materials. Synchrotron measurements used to track recovery in nanocrystalline Ni-0020 (99) showed that, while thermal recovery due to initial point defects is homogeneous, the recovery aided by mechanical deformation (which is different during compression and tension) arises from and perhaps contributes to internal stresses driven by load partitioning between easy and hard grains.…”
Section: Plasticity In Polyphase Alloysmentioning
confidence: 99%
“…In the system described by Vonk et al (97), deformations and interlayer damage development can be tracked under controlled conditions of humidity in a cardboard. Using a combination of micro-computed tomography and far-field high-energy diffraction, Nair et al (98) track stress partitioning in individual grains of a cement-quartz mixture, demonstrating that the loss of a diffraction peak from a grain can signal the onset of fracture in these granular materials. Synchrotron measurements used to track recovery in nanocrystalline Ni-0020 (99) showed that, while thermal recovery due to initial point defects is homogeneous, the recovery aided by mechanical deformation (which is different during compression and tension) arises from and perhaps contributes to internal stresses driven by load partitioning between easy and hard grains.…”
Section: Plasticity In Polyphase Alloysmentioning
confidence: 99%